Silvicultural systems - Matthews, John D. (Clarendon Press,Oxford University Press, 1999)
This book describes the theoretical basis and practical application of 20 diverse silvicultural systems for the benefit of ecologists, land-use managers and other professionals. These systems offer the key to regenerating, tending, and harvesting forests in an era of rapid deforestation and increasing demand for wood as fuel and building material. The approaches described here are being used successfully in widely different parts of the world, from Europe to the tropical rain forests, where reduced forest areas must be carefully managed in order to produce the highest possible sustained yield of timber products compatible with environmental protection and preservation. The systematic presentation and discussion of advantages and disadvantages of each program enables readers to select and apply the program most suitable for their needs